2021
DOI: 10.1186/s12889-021-12017-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the change trajectory of sleep duration and its associated factors: based on an 11-year longitudinal survey in China

Abstract: Background Sleep duration is a vital public health topic, yet most existing studies have been limited to cross-sectional surveys or inconsistent classifications of sleep duration categories, and few characterized its continuous development process. The current study aimed to depict its change trajectory in the general population and identify associated factors from a dynamic perspective. Methods A total of 3788 subjects (45.4% male, mean age 46.72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…The prevalence of sleep deprivation among college students in China is significantly higher than Chinese population. Fang et al (2021) reported the prevalence was 23.6%, 25.3%, 28.9%, 31.9%, and 33.1% in 2004, 2006, 2009, 2011, and 2015 respectively among the Chinese population. It suggests that sleep deprivation is more severe among college students.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The prevalence of sleep deprivation among college students in China is significantly higher than Chinese population. Fang et al (2021) reported the prevalence was 23.6%, 25.3%, 28.9%, 31.9%, and 33.1% in 2004, 2006, 2009, 2011, and 2015 respectively among the Chinese population. It suggests that sleep deprivation is more severe among college students.…”
Section: Discussionmentioning
confidence: 92%
“…Two explanations were proposed for this phenomenon. First, due to the nation’s rapid economic development, especially the establishment of logistical supply chains and internet-based technologies, which give people access to media and entertainment conveniently, people are sleeping shorter ( Fang et al, 2021 ). Secondly, most Chinese college students are free from the supervision of their parents and start to live independently when they go to college.…”
Section: Discussionmentioning
confidence: 99%
“…Even such a minor curtailment accumulates to more than an hour of missed sleep per week. These sleep deficits may be especially severe for some individuals or regions owing to social inequities in sleep opportunities and broader societal changes that undermine sleep (Grandner, 2017;Fang et al, 2021;Caraballo et al, 2022).…”
Section: Sleep-related Fatigue Among Subjects In the Criminal Justice...mentioning
confidence: 99%
“…As a modifiable lifestyle, sleep is closely associated with cardiovascular functions, such as heart rate, blood pressure, or cardiac output [ 2 ]. Changes in society and technology influence sleep in many aspects, including sleep quality and sleep duration in the population [ 3 , 4 ]. A study on sleep trends among adults in the United States showed that the probability of short sleep in the population gradually increased from 2007 to 2017 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%